Curcumin as an Adjuvant to Cancer Immunotherapy - Paul, Silpita; Sa, Gaurisankar (Frontiers in Oncology, 2021)
The components of the immune system play a very sincere and crucial role in combating tumors. But despite their firm efforts of elimination, tumor cells cleverly escape the surveillance process by adopting several immune evasion mechanisms. The conversion of immunogenicity of tumor microenvironment into tolerogenic is considered as a prime reason for tumor immune escape. Therapeutically, different immunotherapies have been adopted to block such immune escaping routes along with better clinical outcomes. Still, the therapies are haunted by several drawbacks. Over time, curcumin has been considered as a potential anti-cancer molecule. Its potentialities have been recorded against the standard hallmarks of cancer such as continuous proliferation, escaping apoptosis, continuous angiogenesis, insensitivity to growth inhibitors, tissue invasion, and metastasis. Hence, the diversity of curcumin functioning has been already established and exploration of its application with immunotherapies might open up a new avenue for scientists and clinicians. In this review, we briefly discuss the tumor’s way of immune-escaping, followed by various modern immunotherapies which have been used to encounter the escaping paths and their minute flaws. Finally, the conclusion has been drawn with the application of curcumin as a potential immune-adjuvant, which fearlessly could be used with immunotherapies for best outcomes.